ISPC Commentary on the Proposal for CRP1.1 - April 2011 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
ISPC Commentary on Proposal CRP 1.1: Integrated Agricultural Production Systems for the Poor and Vulnerable in Dry Areas (Version of 28 February 2011).